Validity of a Coastal Environments-Based Physics Learning Module on the Theme of Temperature and Heat - Deni Irawan; Trapsilo Prihandono; Lailatul Nuraini (Universitas Lambung Mangkurat, 2020)
Researchers have developed the coastal environments-based physics learning module. One of the quality modules developed can be seen from its validity. This research aims to describe the validity of the coastal environments-based physics learning module on the theme temperature and heat. The technique of collecting data is used a validation sheet by four validators, namely two as expert validators and two as validator practitioners. The validity aspects of the experts assessed are construct, content, and language. Aspects of validity seen from practitioners are relevance, accuracy, readability, and language. The criteria for stating the quality of the physics module developed in each component consist of four evaluations, 1) invalid, 2) less valid, 3) valid, 4) very valid. The results of this research indicated that the expert validity was 3.38 with a very valid category; also that practitioner validity is 3.64 with a very valid category. Thus, a physics learning module insight the coastal environment could be used in learning to observe aspects of quality from other aspects such as practicality and effectiveness.